Fenomenologi Sebagai Metode dalam Penelitian Pertunjukan Teater Musikal - Suyanto Suyanto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
This article explains about musical theater as an interesting phenomenon in this millennial era. The meeting of the idealism of conveying the ideas of artists through works and the audience’s demands of entertainment needs to be studied. Phenomenology, a study in philosophy that studies humans as a phenomenon, is the approach used in this study. The purpose of this paper is to look for something behind the phenomenon of musical theater performances. It seems that musical theater artists and the audiences have not paid much attention to the qualified concept of music but tends to the vulgar and glamorous arts. essentially, music in the musical theater is not just an accompaniment but also to be an amplifier and stabilizer. Nevertheless, the presence of music also gives a beautiful touch for more interesting and entertaining appearance. Keywords: musical theater, music, phenomenology